KERAGAAN PRODUKSI BENIH KEDELAI DI PROVINSI JAMBI - Hery Nugroho; Yardha . (Jurnal Agroekoteknologi, 2013)
National soybean area harvested in the last decade tend to decline. This requires attention and study to find solutions to existing problems. This study aimed to identify implementation of seed production technology of soybeans in three agroecological land in Jambi Province, study the response of farmers to the technology used. This study was conducted from October 2010 through January 2011 in East Tanjung Jabung (Tidal Land), Tanjung Jabung West (Wetland irrigation) and Tebo Regency (Upland). The method used in this research is secondary data collection on soybean seed production technology that is the recommendation of Research Institute for Legumes and Umbiumbian. Furthermore, the survey method to collect primary data obtained through direct interviews with farmers in East Tanjung Jabung (Tidal Land), Tanjung Jabung West (Wetland irrigation) and Tebo Regency (Upland), Jambi Province. Purposive sampling method by farmers as respondents were taken of each region 10 farmers each breeder. The factors that affect farmers in seed production technologies analyzed in description. The results showed that the technology used in three different agro-ecological land this is due to soybean plants can be grown in various agro ecosystem with soil type, soil fertility, climate, and different cropping patterns so that constraints will differ from one agroecosystem other agroecosystem. With the technology is applied to the land tidal obtain the highest production compared with irrigated land and dry land. This happens because the tidal land application of cultivation technology of soybean seed production were adopted. From the results obtained with the expected higher seed production technology will be improved to increase the extent of unity.